Preferences for oral fluid rapid HIV self-testing among social media-using young black, Hispanic, and white men-who-have-sex-with-men (YMSM): implications for future interventions. (April 2017) - Merchant, R.C.; Clark, M.A.; Liu, T.; Rosenberger, J.G.; Romanoff, J.; Bauermeister, J.; Mayer, K.H.
Abstract: Objectives: We assessed preferences of social media-using young black, Hispanic and white men-who-have-sex-with-men (YMSM) for oral fluid rapid HIV self-testing, as compared to other currently available HIV testing options. We also identified aspects of the oral fluid rapid HIV self-test that might influence preferences for using this test instead of other HIV testing options and determined if consideration of HIV testing costs and the potential future availability of fingerstick rapid HIV self-testing change HIV testing preferences. Study design: Anonymous online survey. Methods: HIV-uninfected YMSM across the United States recruited from multiple social media platforms completed an online survey about willingness to use, opinions about and their preferences for using oral fluid rapid HIV self-testing and five other currently available HIV testing options. In a pre/post questionnaire format design, participants first indicated their preferences for using the six HIV testing options (pre) before answering questions that asked their experience with and opinions about HIV testing. Although not revealed to participants and not apparent in the phrasing of the questions or responses, the opinion questions concerned aspects of oral fluid rapid HIV self-testing (e.g. its possible advantages/disadvantages, merits/demerits, and barriers/facilitators). Afterward, participants were queried again about their HIV testing preferences (post). After completing these questions, participants were asked to re-indicate their HIV testing preferences when considering they had to pay for HIV testing and if fingerstick blood sample rapid HIV self-testing were an additional testing option. Aspects about the oral fluid rapid HIV self-test associated with increased preference for using the test (post-assessment vs pre-assessment of opinion topics) were identified through multivariable regression models that adjusted for participant characteristics. Results: Of the 1975 YMSM participants, the median age was 22 years (IQR 20–23); 19% were black, 36% Hispanic, and 45% white; and 18% previously used an oral fluid rapid HIV self-test. Although views about oral fluid rapid HIV self-testing test were favorable, few intended to use the test. Aspects about the oral fluid rapid HIV self-test associated with an increased preference for using the test were its privacy features, that it motivated getting tested more often or as soon as possible, and that it conferred feelings of more control over one's sexual health. Preferences for the oral fluid rapid HIV self-test were lower when costs were considered, yet these YMSM were much more interested in fingerstick blood sampling than oral fluid sampling rapid HIV self-testing. Conclusions: Despite the perceived advantages of the oral fluid rapid HIV self-test and favorable views about it by this population, prior use as well as future intention in using the test were low. Aspects about oral fluid rapid HIV self-testing identified as influential in this study might assist in interventions aimed to increase its use among this high HIV risk population as a means of encouraging regular HIV testing, identifying HIV-infected persons, and linking them to care. Although not yet commercially available in the United States, fingerstick rapid HIV self-testing might help motivate YMSM to be tested more than oral fluid rapid HIV self-testing. Highlights: Few black, Hispanic, or white social media-using YMSM have used or plan to use oral fluid rapid HIV self-testing. Opinions identified in the study might assist future interventions to influence YMSM to use the oral fluid rapid HIV self-test. YMSM are more interested in fingerstick than oral fluid rapid HIV self-testing, despite its lack of commercial availability.